INFLUENCE OF LAND USE IN THE QUALITY OF GROUNDWATER IN WATERSHEDS IN THE SOUTHERN PART OF ESPIRITO SANTO, BRAZIL - Bertossi, Ana Paula Almeida; de Menezes, João Paulo Cunha; Firmino, Elziane Favoreto Elves; Neves, Mirna Aparecida; Garcia, Giovanni de Oliveira; Cecílio, Roberto Avelino (Águas Subterrâneas, 2011)
The groundwater has assumed an increasingly important source of supply, so studies should be directed to this type of water resource. Thus, the objective was to identify the alterations in the quality of groundwater in watersheds occupied by different agroforestry uses (forest, coffee and pasture) in the south of Espirito Santo. The area with coffee had a higher pH than the others areas in the two study periods and the area under pasture had a higher electrical conductivity. The nitrate and nitrite levels remained below the maximum allowed by Brazilian National Council legislation (CONAMA) 396/08 and in some cases had become so low that the equipment failed to detect them, as well as ammonia nitrogen.